2020
DOI: 10.1021/acsomega.9b04205
|View full text |Cite
|
Sign up to set email alerts
|

Waterproof Flexible Polymer-Functionalized Graphene-Based Piezoresistive Strain Sensor for Structural Health Monitoring and Wearable Devices

Abstract: In recent times, flexible piezoresistive polymer nanocomposite-based strain sensors are in high demand in wearable devices and various new age applications. In the polymer nanocomposite-based strain sensor, the dispersion of conductive nanofiller remains challenging due to the competing requirements of homogenized dispersion of nanofillers in the polymer matrix and retaining of the inherent characteristics of nanofillers. In the present work, waterproof and flexible poly(vinylidene difluoride) (PVDF) with a po… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
27
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 46 publications
(33 citation statements)
references
References 58 publications
1
27
1
Order By: Relevance
“…In fact, it is demonstrated that the percolation threshold θ c of the obtained samples is achieved at a GNP weight fraction around 0.55% wt. This value is lower with respect to the one recently observed in case of hydrogen exfoliated graphene in a PVDF polymer matrix [26], and is comparable with the one obtained using CNTs as nanofillers [34]. Furthermore, it is worth noting that the perfect integration of GNPs inside the polymer matrix among an optimum dispersion of them, without agglomerations or defects, allowed us to reach electrical conductivity values one or two order of magnitudes higher than the ones of PVDF nanocomposites filled with other graphene-based nanofillers, such as reduced graphene oxides [13], CNTS [27], and hydrogen exfoliated graphene [26].…”
Section: Discussioncontrasting
confidence: 74%
See 4 more Smart Citations
“…In fact, it is demonstrated that the percolation threshold θ c of the obtained samples is achieved at a GNP weight fraction around 0.55% wt. This value is lower with respect to the one recently observed in case of hydrogen exfoliated graphene in a PVDF polymer matrix [26], and is comparable with the one obtained using CNTs as nanofillers [34]. Furthermore, it is worth noting that the perfect integration of GNPs inside the polymer matrix among an optimum dispersion of them, without agglomerations or defects, allowed us to reach electrical conductivity values one or two order of magnitudes higher than the ones of PVDF nanocomposites filled with other graphene-based nanofillers, such as reduced graphene oxides [13], CNTS [27], and hydrogen exfoliated graphene [26].…”
Section: Discussioncontrasting
confidence: 74%
“…Due to their outstanding properties, GNP-filled polymer composites have been widely investigated in various engineering applications, including electromagnetic compatibility [ 18 , 19 , 20 ], structural sensing and monitoring [ 21 , 22 , 23 , 24 ]. Different polymer matrices have been explored, such as polystyrene [ 17 , 20 ], epoxy-based vinyl ester resins [ 18 , 19 , 24 ], polydimethylsiloxane [ 5 , 22 ], polyurethane [ 25 ], and polyvinylidene fluoride (PVDF) [ 23 , 24 , 26 , 27 , 28 ]. Among them, PVDF is garnering ever growing interest for sensing applications owing to its uncommon chemical resistance and thermal mechanical physical properties, including piezoresistive and piezoelectric ones [ 29 , 30 ].…”
Section: Introductionmentioning
confidence: 99%
See 3 more Smart Citations